The Effect of Halliwick Method on Aquatic Skills of Children with Autism Spectrum Disorder - Vodakova, Eliska; Chatziioannou, Dimitrios; Jesina, Ondrej; Kudlacek, Martin (International journal of environmental research and public health, 2022)
Background: Swimming and the skills associated with participation in the aquatic environment tend to be an integral part of the movement literacy complex. Non-participation then affects the safety of movement in the aquatic environment and may also be the reason for the limitation of movement, psychological, and social development compared to peers. Methods: This study is a single-subject research study. The aim of this study is to evaluate the effect of a seven-week intervention program of the Halliwick method in the development of aquatic skills, gross motor skills, and mental skills relevant for aquatic competence for children with autism spectrum disorder. Seven children with autism spectrum disorder participated in swimming classes for a two-week baseline period and a seven-week intervention program of the Halliwick method, one time per week. To measure the effect in the field of aquatic skills, we used the Alyn Water Orientation Test 1. To determine the level of gross motor skills, we used the Gross Motor Function Measure test. Results: There was an improvement in aquatic skills and gross motor skills in seven participants; two of them did not improve in mental adjustment oriented to the breathing control sections in the water.